FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INISIASI MENYUSUI DINI (IMD) DI PUSKESMAS BUTAR KECAMATAN PAGARAN KABUPATEN TAPANULI UTARA TAHUN 2020 - Fransiska Debataraja; Nova Sontry Node Siregar; Winta Mariana Batubara (Jurnal Ilmiah Kebidanan Imelda, 2021)
Early Initiation of Breastfeeding (IMD) is an opportunity given to babies immediately after birth by placing the baby on the mother's stomach, then the baby is allowed to find the mother's nipple and breastfeed within the first hour after birth. The UNICEF organization Says that IMD is so important for babies that it calls it the baby's first vaccine. The purpose of this study was to determine the factors related to the implementation of Early Breastfeeding Initiation (IMD) at Butar Puskesmas, Pagaran District, Tapanulu Utara Regency in 2020. This type of research is a descriptive quantitative study using a cross sectional design or approach looking at the relationship between the independent and dependent variables. The total population of 30 people was used with a total sampling technique in which the entire population was sampled so that the sample size was 30 people. Data were collected by means of a questionnaire, then the data were processed using the chi-square test. The results of the study using the chi-square test with a confidence level of 95% (α = 0.05) showed that there was no relationship between the type of labor and the results of the Fisher's Exact Test with a confidence level of 95% and df = 1 obtained x2 count (0.597) <x2. table (3,841), there is a relationship of knowledge df = 2 obtained x2 count (10.425)> x2 table 5,991, there is a relationship between husband's support for Fisher's Exact Test with a confidence level of 95% (α = 0.05) and df = 1 obtained p value = 0.000 ( p <0.05), there is a relationship between support for health workers and df = 2, it is obtained x2 count (8,450)> n x2 table (5,991). It is expected that respondents will know the information provided by health workers or from the mass media about the provision and implementation of Early Breastfeeding Initiation (IMD).